Program Kampanye #Budayabeberes Terhadap Partisipasi Masyarakat Untuk Membuang Sampah Sendiri - Siti Khadijah (Universitas Bina Sarana Informatika, 2021)
Currently there are many problems in the environmental sector, such as a lack of public awareness in sorting and disposing of waste. Therefore, one of the companies that is actively conducting campaigns to reduce this problem is KFC Indonesia. KFC spreads its #budayabeberes campaign message via Instagram. The purpose of this study was to determine the effect of the #budayabeberes campaign on community participation in disposing of their own waste. This research used descriptive explanative method, with a quantitative approach. The sampling technique used accidental sampling. The data collection techniques used questionnaires and interviews. The analysis technique used linear regression. The results in this study state that the cultural campaign program carried out on Instagram has an influence of 46.1% and the remaining 53.9% is influenced by other factors such as interest from participants, gifts from an activity, the existence of benefits from activities, and outside motivation. The #budayabeberes campaign program has a positive and significant effect on community participation in disposing of their own waste with a coefficient value of 1.391